Clinical pharmacokinetics of nadolol: A systematic review. (30th August 2022) - Kalsoom, Samia; Zamir, Ammara; Rehman, Anees ur; Ashraf, Waseem; Imran, Imran; Saeed, Hamid; Majeed, Abdul; Alqahtani, Faleh; Rasool, Muhammad Fawad
Abstract: What is known and objective: Nadolol is a non‐selective beta‐adrenergic antagonist that is used for the treatment of hypertension and angina. The primary route for its administration is oral. It is given once daily as it has a longer half‐life ( t ½). The purpose of conducting this systematic review is to provide a comprehensive view of all the available pharmacokinetic (PK) data on nadolol in humans. This review aimed to systematically collate and analyze publish data on the clinical PK of nadolol in humans and this can be beneficial for the clinicians in dosage adjustments. Methods: Two electronic databases PubMed and Google Scholar were used for conducting a systematic literature search. All the relevant articles containing PK data of nadolol in humans were retrieved. A total of 1275 articles were searched from both databases and after applying eligibility criteria finally, 22 articles were included for conducting the systematic review. Results and discussion: The area under the plasma concentration curve (AUC) and maximum plasma concentration ( C max ) of nadolol increased in a dose‐dependent manner. The t ½ of nadolol was increased to double (18.2–68.6 h) in the patients with chronic kidney disease while the serum t ½ became shorter (3.2–4.3 h) when administered to the children. The bioavailability of nadolol was greatly reduced by the coadministration of green tea. Nadolol can be effectively removed by hemodialysis. It undergoes enterohepatic circulation thus activated charcoal decreased its bioavailability. What is new and conclusion: Since, there is no previous report of a systematic review on the PK of nadolol, the current review encompasses all the relevant published articles on nadolol in humans. The analysis and understanding of PK parameters (AUC, C max, and t ½) of nadolol may be helpful in the development and evaluation of PK models. Abstract : This systematic review aimed to collect and analyse all the PK data of nadolol from studies conducted in healthy and diseased populations. Among the total 22 studies, 03 were IV, 07 were in diseased population, 06 studies were focused on drug–drug and drug‐food interactions, and 01 study included lactating mothers. The analysis of these studies shows that the PK parameters such as C max, and AUC proportionally increase with dose in healthy subjects while the serum t ½ of nadolol was greatly increased in the patients with chronic kidney disease. Moreover, the bioavailability of nadolol was significantly reduced with the co‐administration of green tea. The knowledge of all these altered PK parameters with disease states can be useful for making individualized dose adjustments.